Basic Properties of the Integral Notes

# Note that b is now the lower limit on the integral

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 1 5 3 3 5 1 7 b−a 7 = f a+ b +f a+ b +f a+ b +f a+ b 8 8 8 8 8 8 8 8 4 b−a 4 f a+ (2) a We’re now going to write out the midpoint Riemann sum approximation to b f (x) dx with 4 subintervals. Note that b is now the lower limit on the integral and a is now the upper limit on the integral. This is likely to cause confusion when we write out the Riemann sum, 3 January 13, 2014 so we’ll temporarily rename b to A and a to B . The midpoint Riemann sum approximation B to A f (x) dx with 4 subintervals is 3B −A 5B −A 1B −A +f A+ +f A+ +f 24 24 24 1 3 5 5 3 1 7 = f A+ B +f A+ B +f A+ B +f A+ 8 8 8 8 8 8 8 f A+ A+ 7 B 8 7B −A 24 B−A 4 B−A 4 Now setting A = b and B = a, we have that the midpoint Riemann sum approximation to a f (x) dx with 4 subintervals is b f 7 1 5 3 3 5 1 7 b+ a +f b+ a +f b+ a +f b+ a 8 8 8 8 8 8 8 8 a−b 4 (3) The curly brackets in (2) and (3) are equal to each other — the terms are just in the reverse order. So (3)= −(2). The same computation with n subintervals shows that the midpoint a b Riemann sum approximations to b f (x) dx and a f (x) dx with n subintervals are negatives a b of each other. Taking the limit n → ∞ gives b f (x) dx = − a f (x) dx. Example 4 Recall that if x ≥ 0 x |x| = −x if x ≤ 0 So 1 −1 0 f |x| dx = −1 0 = −1 1 f |x| dx + f |x| dx 0 1 f (−x) dx + f (x) dx 0 Example 4 4 January 13, 2014 Theorem 5 (Inequalities for Integrals). Let a ≤ b be real numbers and let the functions f (x) and g (x) be integrable on the interval a ≤ x ≤ b. (a) If f (x) ≥ 0 for all a ≤ x ≤ b, then a b f (x) dx ≥ 0 (b) If there are constants m and M such that m ≤ f (x) ≤ M for all a ≤ x ≤ b, then a m(b − a) ≤ f (x) dx ≤ M (b − a) b (c) If f (x) ≤ g (x) for all a ≤ x ≤ b, then a f (x) dx ≤ b (d) We have b g (x) dx a a b a f (x) dx ≤ |f (x)| dx b Proof. (a) Just says that if the curve y = f (x) lies above...
View Full Document

## This note was uploaded on 02/12/2014 for the course MATH 101 taught by Professor Broughton during the Spring '08 term at The University of British Columbia.

Ask a homework question - tutors are online